Capital Structure, Wage Bargaining and Employment - Erkki Koskela; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2000)
We offer a unified framework to analyze the determination of employment, employee effort, wages, profit-sharing and capital structure when firms face stochastic revenue shocks. We apply a generalized Nash bargaining solution, which extends the wage bargaining literature by incorporating efficiency wage considerations, profit-sharing and capital structure. The profit-sharing instrument is demonstrated to have positive effort-augmenting and wage-moderating effects, which exactly offset the negative dilution effect in equilibrium. Leverage is shown to decrease employment and to have a strategic commitment value as a wage-moderating effect for firms facing unions in bilateral wage negotiations. Finally, some implications for equilibrium unemployment are characterized.
Keywords: 330; Wage bargaining; profit sharing; capital structure; employment